This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Solution 1:
x 4 + 2 x 3 + 3 x 2 + 2 x + 1 = ( x 2 + x + 1 ) 2 = 0
⇒ x 2 + x + 1 = 0
⇒ ( x + 1 ) 2 − x = 0
⇒ ( x + 1 ) 2 = x
Since ( x + 1 ) 2 ≥ 0 , x has to be a non-negativ number, but it contradict that x 2 + x + 1 = 0 . So the equation hasn't got any solution.
Solution 2:
( x 4 + 2 x 3 + x 2 ) + x 2 + ( x 2 + 2 x + 1 ) = 0
⇒ x 2 ( x + 1 ) 2 + x 2 + ( x + 1 ) 2 = 0
On the left side there are only perfect squares, so the left side is non-negativ. If the sum of three non-negativ numbers is 0 , then all of them is 0. But x 2 and ( x + 1 ) 2 can't be 0 at the same time, so the equation hasn't got any solution.